One-shot synthesis and solution properties of ROS/pH responsive methoxy poly(ethylene glycol)-b-polycarbonate. Issue 17 (2nd April 2019) - Zhang, Yan; Xu, Yue; Wei, Chao; Sun, Chuanhao; Yan, Bingkun; Hu, Jieni; Lu, Wei
Abstract : A one-shot method was employed to synthesize ROS/pH responsive methoxy poly(ethylene glycol)- b -polycarbonate (mPEG- b -poly(MN- co -MSe)) with the selenide and tertiary amine groups situated on the backbone. Abstract : Herein, we reported a dual-responsive methoxy poly(ethylene glycol)- b -polycarbonate (mPEG- b -poly(MN- co -MSe)) by installing selenide and tertiary amine groups onto the backbone via a one-shot enzyme-catalyzed ring-opening copolymerization. The structure of the copolymers was confirmed by NMR, FTIR and SEC. The amphiphilic copolymers can self-assemble to nanosized micelles, and the micelles had excellent ROS/pH responsive behavior, which was attributed to the enhanced hydrophilicity by the oxidation of the selenide groups to hydrophilic selenoxide or selenone, as well as the protonation of tertiary amine groups. The oxidation mechanism was clarified by 77 Se-NMR, FTIR and TGA data. Thereafter, UV, DLS and TEM techniques were employed to demonstrate the variation of the transmittance, size, and morphology of the micelles. Furthermore, MTT assays showed that the selenide- and amine-containing polycarbonates and the oxidized products were nontoxic up to a tested concentration of 200 μg mL −1 . Therefore, these results proved that the micelles could provide unique dual ROS and pH responsiveness, making them extremely attractive for cancer therapy.